Urban sprawl and its financial cost: - A conceptual framework - Osman, Shahriza; Nawawi, Abdul Hadi; Abdullah, Jamalunlaili (Canadian Center of Science and Education, 2008)
Urban sprawl has been recognized as an urban expansion which leads to undesirable impacts in terms of sacrifice of farmland and loss of amenity benefits from open space on the urban fringe.Integral to the negative impacts of sprawl is the higher financial costs that have to be incurred mainly through expenses related to the physical development in an unplanned manner.A framework of understanding sprawl and its financial cost in a developing country’s context namely Malaysia is proposed based on four (4) strategic steps namely, sprawl identification, measurement, decision and financial analysis utilizing the differential costs approach by comparing financial costs of development under unplanned sprawl and a planned strategy. The framework would provide a structured insight into quantifying the financial costs of sprawl to guide economists and urban planners in making a decision pertaining to urban development.